The acceptability of dietary tools to improve maternal and child nutrition in Western Kenya - Kram, N.; Melgen, S.; Kedera, E.; Collison, D.K.; Colton, J.; Blount, W.; Grant, F.; Girard, Amy W. (Cambridge University Press, 2016)
Dietary practices in Kenya often fail to provide adequate nutrition during the first 1000 days of life, from conception to 2 years of age. We developed and qualitatively assessed the acceptability of easy-to-use dietary tools consisting of a marked bowl, slotted spoon and illustrated counselling card to support appropriate dietary practices during pregnancy, exclusive breast-feeding and complementary feeding of children aged 6–24 months.We conducted qualitative research to assess community acceptability and obtain feedback on the design of the dietary tools.This research took place in urban and rural communities in Western Kenya.We conducted twelve focus group discussions with community members (mothers, husbands, mothers-in-law, community leaders) and five interviews with government nutritionists to assess acceptability and obtain recommendations on design and delivery of the tools. We conducted 24–28 d of user testing with fourteen pregnant women, fourteen breast-feeding women and thirty-two mothers with infants aged 6–18 months.Tools were positively received by communities. Mothers perceived improvements in their own and their children’s food intakes including quantity, frequency, consistency and diversity. Many attributed perceived own and child’s weight gain and/or increased energy to tool use. A minority reported using the bowl for other activities (n 9) or not using the bowl due to food insecurity (n 5).Results suggest that such tools have the potential to positively impact maternal and child dietary practices. Future work should quantitatively assess the impact on diet and nutrition outcomes and the underlying behavioural domains associated with changes.